A case of gastric carcinoma presenting with a metastatic cutaneous nodule in the face - Paul, Negine; Surendran, Suraj; Yakob, Myla; Abraham, Vijay (Indian Journal of Case Reports, 2020)
Skin is an uncommon site for distant metastasis and is reported to be involved in about 0.7–9% of all patients with cancer. Although metastasis to the skin usually appears in the advanced stage of the disease, they can also be the first sign of internal malignancy in a small group of patients. It is extremely rare for gastric cancer to present with a cutaneous metastatic nodule in the face. Herein, we report the case of a young patient who presented with a cutaneous nodule in his left cheek, which on evaluation was found to be a metastatic cutaneous nodule from carcinoma stomach. This case highlights its rarity and emphasizes the need for clinical vigilance in diagnosing this condition.